2013
DOI: 10.1039/c3ja50059d
|View full text |Cite
|
Sign up to set email alerts
|

A novel ToF-SIMS operation mode for improved accuracy and lateral resolution of oxygen isotope measurements on oxides

Abstract: Oxygen isotope exchange with subsequent time-of-flight secondary ion mass spectrometry (ToF-SIMS) is a highly valuable tool for determining oxygen diffusion coefficients in oxides. Since ToF-SIMS analysis enables an elemental and chemical mapping, it can also be used to visualize oxygen exchange-active zones by determining the local oxygen isotopic fraction. However, measuring accurate isotopic fractions can be a challenging analytical task owing to secondary ion interaction and signal saturation, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 72 publications
0
58
0
Order By: Relevance
“…Detector dead time is a well-known problem in time-of-flight mass spectrometry, and correction methods based on Poisson statistics have been developed [40] and are now standard protocol in quantitative TOF-SIMS analysis [4,41,42]. An interlaboratory study involving 21 TOF-SIMS instruments has demonstrated that this correction is generally applicable and robust [43].…”
Section: Ion Detection and Countingmentioning
confidence: 98%
“…Detector dead time is a well-known problem in time-of-flight mass spectrometry, and correction methods based on Poisson statistics have been developed [40] and are now standard protocol in quantitative TOF-SIMS analysis [4,41,42]. An interlaboratory study involving 21 TOF-SIMS instruments has demonstrated that this correction is generally applicable and robust [43].…”
Section: Ion Detection and Countingmentioning
confidence: 98%
“…32 This can be improved by bursting the beam in a similar way to that used in the "burst mode" measurements. This also has the effect of further decreasing the time-averaged primary current.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…It would be possible to mitigate the saturation of 16 O which leads to the inaccurate value for C1 by further reducing the PI current (note we used a pulsed current of 0.068 pA@50 μs, which is at the low end of the range 0.03−0.05 pA @100 μs specified by Holzlechner et al). 32 However, decreasing the PI current further would decrease the precision of the measurement of 18 O SI intensity, adversely affecting the precision of the measured C1. Both BA and CBA modes avoid dead-time effects in the detector by decreasing the PI intensity, which enables the detection of the species with high ion yields and/or high concentration, such as 16 O, by globally decreasing the intensity of the spectrum.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The measurements were carried out on a TOF-SIMS IV instrument (ION-TOF GmbH, Muenster, Germany). A pulsed bismuth primary ion gun (25 keV, Bi 3 þ þ ) was used in the "collimated burst alignment" (CBA) mode enabling high lateral resolutions below 100 nm [18,27]. Additionally, to ToF-SIMS imaging in the CBA mode, high mass resolution spectra were acquired using the high current bunched mode (HCBU) to differentiate contributions of H 2 À and D À and OH 2 À and OD À secondary ions (SI) to the peaks at m/z ¼ 2 and m/ z¼18, respectively.…”
Section: Time-of-flight Secondary Ion Mass Spectrometry (Tof-sims)mentioning
confidence: 99%